An assessment of the disaster preparedness of the city of Gweru - Marecha, Audrey Thandazani (Midlands State University, 2017)
The research was on the disaster preparedness of the city of Gweru. Using qualitative research methodology the researcher managed to collect data that was used in the research. The research discovered that there is need for strengthening of the disaster preparedness especially in the field of community involvement. Disaster preparedness has proven to be viable way of effective response hence the extent of the city preparedness affected its response to disasters. However the disaster preparedness has improved for the past five (5) years.